2008
DOI: 10.1111/j.1365-280x.1998.00137.x
|View full text |Cite
|
Sign up to set email alerts
|

The effects of Malassezia on pro-inflammatory cytokine production by human peripheral blood mononuclear cells in vitro

Abstract: Malassezia spp., the causative agents of pityriasis versicolor, are members of the normal human cutaneous microflora. Utilizing a combination of both enzyme‐linked immunosorbent assay (ELISA) and bioassay, we have investigated the ability of both formalin‐preserved and viable Malassezia (serovars A, B and C) to modulate pro‐inflammatory cytokine (IL‐6, IL‐1β and TNF‐α) release by human peripheral blood mononuclear cells (PBMNC) in vitro, over a 48‐h co‐incubation period. The results demonstrated that formalin‐… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 0 publications
0
21
2
Order By: Relevance
“…The results of the study of Kesavan et al. show that Malassezia yeast significantly reduces the production of pro‐inflammatory cytokines, 29 which is related to the presence of lipid‐rich microfibrillar layer surrounding yeast cells. High quantity of lipid may prevent the yeast cell from inducing inflammation what is in consistent with their commensal status.…”
Section: Discussionmentioning
confidence: 99%
“…The results of the study of Kesavan et al. show that Malassezia yeast significantly reduces the production of pro‐inflammatory cytokines, 29 which is related to the presence of lipid‐rich microfibrillar layer surrounding yeast cells. High quantity of lipid may prevent the yeast cell from inducing inflammation what is in consistent with their commensal status.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that Malassezia furfur modulates proinflammatory and immunomodulatory cytokine synthesis in the keratinocyte cell line by suppressing interleukin‐1α (IL‐1α), IL‐6 and tumor necrosis factor‐α (TNF‐α) and by upregulating IL‐10 and TGF‐β1 4 . When Malassezia yeast cells were co‐cultured with human peripheral blood mononuclear cells (PBMNC), they were found to be capable of significantly decreasing the release of IL‐6, IL‐1β, and TNF‐α by human PBMNC 5 . However, the extraction of lipid from the yeast cells reversed this capacity to reduce proinflammatory cytokine synthesis; this suggests that the lipid microfibrillar layer of Malassezia spp.…”
Section: Discussionmentioning
confidence: 99%
“…Removal of the capsule-like layer reverses the suppression of cytokine production by monocytes 7 . Kesavan et al 6 have examined the effect of the Malassezia species with and without the capsular layer on the cytokine production by monocytes. As a result, the levels of IL-1α, IL-6 and TNF-α production were lower in the Malassezia with the capsular layer, suggesting that the capsule suppresses the release of proinflammatory cytokine and it prevents an inflammatory response 7 .…”
Section: Discussionmentioning
confidence: 99%
“…It is thought that the lipid-rich layers play a critical role in physiologic and pathologic conditions. According to Kesavan et al 6 , Malassezia furfur (M. furfur)…”
Section: Introductionmentioning
confidence: 99%